Towards a Service Supply Chain Approach for Public Service Management - Isabell Storsjö; Martins, A. (XXIII Annual Conference of the International Research Society for Public Management, 2019)
Modern public services are characterised by inter-organisational relationships, multi-actor policy making, and coproduction. These are also aspects of service supply chain management, but there are specificities. The aim of this conceptual paper is to develop propositions based on existing research to further the knowledge in the intersection of (service) supply chain management and public management. The four propositions relate to: the structure of public service provision; for whom public services are provided; what is it that flows through the public service supply chain; and the role of coordination as a component of management in the public service supply chain